Crotacetin, a novel snake venom C-type lectin, is homolog of convulxin - Rádis-baptista, G.; Moreno, F. B. M. B.; Nogueira, L. L.; Martins, A. M. C.; Toyama, D. O.; Toyama, M. H. [UNESP]; Azevedo Jr, W. F. [UNESP]; Cavada, B. S.; Yamane, T. (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Snake venom (sv) C-type lectins encompass a group of hemorrhagic toxins, which are able to interfere with hemostasis. They share significant similarity in their primary structures with C-type lectins of other animals, and also present a conserved carbohydrate recognition domain (CRD). A very well studied sv C-type lectin is the heterodimeric toxin, convulxin (CVX), from the venoms of South American rattlesnakes, Crotalus durissus terrificus and C. d. cascavella. It consists of two subunits, alfa (CVXalpha , 13.9 kDa) and beta (CVXbeta , 12.6 kDa), joined by inter and intra-chain disulfide bounds, and is arranged in a tetrameric alpha4beta4 conformation. Convulxin is able to activate platelet and induce their aggregation by acting via p62/GPVI collagen receptor. Several cDNA precursors, homolog of CVX subunits, were cloned by PCR homology screening. As determined by computational analysis, one of them, named crotacetin beta subunit, was predicted as a polypeptide with a tridimensional conformation very similar to other subunits of convulxin-like snake toxins. Crotacetin was purified from C. durissus venoms by gel permeation and reverse phase high performance liquid chromatography. The heterodimeric crotacetin is expressed in the venoms of several C. durissus subspecies, but it is prevalent in the venom of C. durissus cascavella. As inferred from homology modeling, crotacetin induces platelet aggregation but noticeably exhibits antimicrobial activity against Gram-positive and Gram-negative bacteria.
Keywords: Crotalus durisssus venom; snake venom C-type lectin; homology modeling; platelet aggregation; antimicrobial activity